Analysis of factors affecting employee performance at Tugu Mulyo Community Health Center: A cross-sectional study - Ayu Anggia Trida; Nani Sari Murni; M Prima Cakra Randana (School of Health Sciences Al-Ma'arif, 2025)
Background Employee performance at primary healthcare facilities is crucial for meeting the Minimum Service Standards. At Tugu Mulyo Health Center, several programs failed to meet national targets, allegedly due to poor staff performance. Objective This study aimed to analyze the factors influencing employee performance at Tugu Mulyo Health Center, Ogan Komering Ilir Regency. Methods A quantitative analytic study with a cross-sectional design was conducted involving all 74 health workers using total sampling. Data were collected via validated structured questionnaires covering variables such as competence, motivation, work experience, compensation, workload, and performance. Bivariate analysis was performed using Chi-square tests, and multivariate analysis applied logistic regression to identify dominant factors. Results Bivariate analysis found that only the competency variable had a statistically significant relationship with performance (p = 0.030). Multivariate logistic regression confirmed competency as the dominant factor (OR = 0.311; 95% CI: 0.118–0.819; p = 0.018), explaining 10.2% of the variance in employee performance (pseudo R² = 0.102). Other variables such as motivation, compensation, work experience, and workload were not significantly associated with performance. Conclusion Competency is the dominant factor affecting health worker performance at Tugu Mulyo Health Center. Improving employee competency is critical for achieving optimal performance.